2012
DOI: 10.1097/igc.0b013e318253a9c9
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Single-Center Study of Sentinel Lymph Node Detection in Cervical Carcinoma: Is There a Place in Clinical Practice?

Abstract: Sentinel lymph node detection is an accurate and safe method in the assessment of nodal status in early cervical carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
(20 reference statements)
2
12
0
1
Order By: Relevance
“…In our study, the majority of SLNs were located in the external iliac (38.6%), obturator (25.3%), and internal iliac regions (23.6%), which confirm the distribution of SLNs described by previous studies. 10,12,26,29 Distributions for the common iliac 11,28 and obturator regions 10,26,30 were similar to those reported by other studies. The detection of SLNs in the para-aortic region was low as previously reported (1.5%Y3.5%) in the SENTICOL study 4 and other studies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In our study, the majority of SLNs were located in the external iliac (38.6%), obturator (25.3%), and internal iliac regions (23.6%), which confirm the distribution of SLNs described by previous studies. 10,12,26,29 Distributions for the common iliac 11,28 and obturator regions 10,26,30 were similar to those reported by other studies. The detection of SLNs in the para-aortic region was low as previously reported (1.5%Y3.5%) in the SENTICOL study 4 and other studies.…”
Section: Discussionsupporting
confidence: 86%
“…Few studies have reported the SLN locations by different methods of detection (SPECT/CT scan, gamma probe, and blue dye). 4,11,12,27,28 These studies describe overall SLN locations in different regions of the pelvis, but not all commented on laterality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, presacral SLNs are less often diagnosed during laparoscopic surgery. This observation may be explained in terms of technical diffi culties and that some authors classify the presacral lymph nodes as belonging to the paraaortal [ 35 ] or internal iliac area [ 18 ]. Paraaortal lymph nodes were often detected during the 2-day protocols, which used ultra-small particles (<100 nm).…”
Section: Distribution Of Slnsmentioning
confidence: 89%